The impact of intrafirm incentive conflicts on the interplay between tax incidence and economic efficiency - Fan, Qintao; Johnson, Nicole Bastian; Pfeiffer, Thomas (Contemporary Accounting Research, 2023)
Abstract We study how corporate taxation interacts with intrafirm incentive conflicts between shareholders and managers and how this interaction impacts the firm's economic decisions and outcomes. In our model, investment under asymmetric information facilitates entrenchment and rent extraction by the privately informed manager. We show that when the future investment payoff is exogenous, a corporate tax cut increases managerial rents, reduces pre‐tax investment profitability, increases the firm's optimal investment hurdle rate, and reduces investment. When the manager can exert upfront project development effort to increase the expected investment payoff, a tax rate reduction not only encourages more effort but also leads the firm to increase the investment hurdle rate to curtail rents. In equilibrium, a lower tax rate always benefits the manager, but the sensitivity of the project's return to the manager's effort determines whether the firm will increase or decrease investment in response to a tax cut, and whether the firm's resulting pre‐tax profit will increase or decrease. Overall, our study shows that intrafirm incentive conflicts can be an important factor in the interplay between tax incidence and economic efficiency, two central themes in corporate tax policy debates.